The conjuring 2 [videorecording (DVD)] - Wan, James, 1977-; Wilson, Patrick, 1973-; Farmiga, Vera; Wolfe, Madison (Warner Bros. Entertainment, 2016)
Lorraine and Ed Warren, who, in one of their most terrifying paranormal investigations, travel to north London to help a single mother raising four children alone in a house plagued by malicious spirits.